Homeostatic effects of coagulation protease‐dependent signaling and protease activated receptors. (3rd July 2017) - Isermann, B.
Summary: A homeostatic function of the coagulation system in regard to hemostasis is well established. Homeostasis of blood coagulation depends partially on protease activated receptor (PAR)‐signaling. Beyond coagulation proteases, numerous other soluble and cell‐bound proteases convey cellular effects via PAR signaling. As we learn more about the mechanisms underlying cell‐, tissue‐, and context‐specific PAR signaling, we concurrently gain new insights into physiological and pathophysiological functions of PARs. In this regard, regulation of cell and tissue homeostasis by PAR signaling is an evolving scheme. Akin to the control of blood clotting per se (the fibrin–platelet interaction) coagulation proteases coordinately regulate cell‐ and tissue‐specific functions. This review summarizes recent insights into homeostatic regulation through PAR signaling, focusing on blood coagulation proteases. Considering the common use of drugs altering coagulation protease activity through either broad or targeted inhibitory activities, and the advent of PAR modulating drugs, an in‐depth understanding of the mechanisms through which coagulation proteases and PAR signaling regulate not only hemostasis, but also cell and tissue homeostasis is required.